Trigonometry (repost Reiny)

posted by .

at 1:35am

I posted ;

Write equivalent equations in the form of inverse functions for
a.)x=y+cos theta
b.)cosy=x^2

my answers were
a.)
x= y+ cos theta
cos theta = x-y
theta = cos^-1(x-y)


b.)
cosy=x^2
cos(y) = x^2
y = Cos^-1(x^2)


your post confused me a little. Can you clarify if my answers were wrong.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    put these polar equations into cartesians form: 1) theta=135 degrees 2)rcostheta=-1 for #1 is it like: (-1,1)?
  2. Calculus

    I wanted to confirm that I solved these problems correctly (we had to convert the polar curves to Cartesian equations). 1.rcos(theta)=1 x=1 2.r=2*sin(theta)+2*cos(theta) r^2=2rsin(theta)+2rcos(theta) x^2+y^2=2y+2x (a little unsure …
  3. Physics

    An object is shot at 20m/s at an angle theta. The object lands 24m away. What is the angle?
  4. trigonometry

    can you correct the rest for me please? Express each as a function of theta: a. sin (270deg + theta)= cos theta b. cos (pi + theta)= -cos theta c. tan (810 + theta)= ?
  5. trigonometry

    can you correct the rest for me please? Express each as a function of theta: a. sin (270deg + theta)= cos theta b. cos (pi + theta)= -cos theta c. tan (810 + theta)= ?
  6. Trigonometry

    Write equivalent equations in the form of inverse functions for a.)x=y+cos è b.)cosy=x^2 (can you show how you would solve) a.) x= y+ cos è cos è = x-y theta = cos^-1(x-y) b.) cosy=x^2 cos(y) = x^2 y = Cos^-1(x^2)
  7. Trigonometry(please Clarify)

    I posted before ; Write equivalent equations in the form of inverse functions for a.)x=y+cos theta b.)cosy=x^2 my answers were a.) x= y+ cos theta cos theta = x-y theta = cos^-1(x-y) b.) cosy=x^2 cos(y) = x^2 y = Cos^-1(x^2) your post …
  8. Math - Trigonometry

    Let f(x) be a polynomial such that f(cos theta) = cos(4 theta) for all \theta. Find f(x). (This is essentially the same as finding cos(4 theta) in terms of cos theta; we structure the problem this way so that you can answer as a polynomial. …
  9. Trigonometry

    Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …
  10. Trigonometry

    Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …

More Similar Questions